PERBEDAAN PENYULUHAN MENGGUNAKAN MEDIA KOMIK DAN MEDIA PAMERAN TERHADAP PENGETAHUAN TENTANG GIGI BERLUBANG PADA MURID KELAS IV DAN V DI SDN 1 SUNGAI TIUNG BANJARBARU PROVINSI KALIMANTAN SELATAN - Muhammad Akhya Rusyadi; Fahmi Said; Rasuna Ulfah (JURNAL TERAPIS GIGI DAN MULUT, 2020)
Dental and oral health counseling is an effort to prevent dental and oral health problems, with the achievement of a better level of dental health in the future. Visual messages in the form of images are more easily embedded in the mind of the audience compared to words, so that dental health education can be more effective if it uses media that display images more, especially in the target audience of elementary school students. This study aims to determine the Difference of Counseling Using Comic Media and Exhibition Media on Knowledge of Cavities in Class IV and V Students at SDN 1 Sungai Tiung Banjarbaru. This research method uses analytic research. The number of samples 80 respondents with a sampling technique using total sampling. The results of this study indicate that the increase in comic media with a difference of 2.08 and exhibition media with a difference of 1.13. Based on the Independent T-test, p = 0.031 was obtained with alpha 0.05 so that p <a, meaning Ho was rejected. Based on the results of this study it can be concluded there are differences in counseling using comic media and exhibition media on knowledge about cavities. It is recommended to provide care services at SDN 1 Sungai Tiung Banjarbaru especially promotive activities, namely continuous counseling in order to help students understand dental and oral health issues, especially about cavities. Keywords: Comic media - knowledge-exhibition media about cavities